2014
DOI: 10.1038/cddis.2014.418
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin, a pro-survival player in estrogen receptor α-positive cancer cells

Abstract: Recently, we reported that human neuroglobin (NGB) is a new player in the signal transduction pathways that lead to 17β-estradiol (E2)-induced neuron survival. Indeed, E2 induces in neuron mitochondria the enhancement of NGB level, which in turn impairs the activation of a pro-apoptotic cascade. Nowadays, the existence of a similar pathway activated by E2 in non-neuronal cells is completely unknown. Here, the role of E2-induced NGB upregulation in tumor cells is reported. E2 induced the upregulation of NGB in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
133
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(148 citation statements)
references
References 37 publications
15
133
0
Order By: Relevance
“…These findings indicate a tumor-suppressive function 21 of ERb which is functionally linked to the promotion of apoptosis, 22 the suppression of the malignant transformation, and the 23 inhibition of tumor cells growth [5,33,39,54]. This concept is in 24 agreement with the ERb levels detected in tumor tissues. In fact, 25 the presence of ERb in breast, endometrial, and ovarian tumors is 26 associated with a better prognosis or a longer survival [6,40,51], 27 whereas the level of ERb is significantly decreased in high grade 28 endometrial cancer [14,47].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings indicate a tumor-suppressive function 21 of ERb which is functionally linked to the promotion of apoptosis, 22 the suppression of the malignant transformation, and the 23 inhibition of tumor cells growth [5,33,39,54]. This concept is in 24 agreement with the ERb levels detected in tumor tissues. In fact, 25 the presence of ERb in breast, endometrial, and ovarian tumors is 26 associated with a better prognosis or a longer survival [6,40,51], 27 whereas the level of ERb is significantly decreased in high grade 28 endometrial cancer [14,47].…”
Section: Introductionsupporting
confidence: 78%
“…Indeed, E2 pre-treatment before 504 H 2 O 2 injury significantly reduces the PARP-1 cleavage and the cell 505 viability in DLD-1 cells; whereas in NGB silenced cells the E2 pro-506 survival effect is completely prevented. Intriguingly, our recent 507 data indicate that E2 also induces NGB up-regulation in ERa-508 expressing cancer cells (i.e., breast cancer and hepatoma cell lines) 509where this globin is important for E2-induced cell survival[24].Taken together these results indicate that NGB is an E2-inducible 511 protein in several cell contexts where NGB up-regulation could act Mitochondria act as sentinels of diverse stress signals that 515 emanate from other intracellular organelles as well as from a 516 variety of environmental stress signals such as low nutrient levels,517 increased calcium levels, oxidative stress. In response to theseFig.…”
mentioning
confidence: 93%
“…This evidence prompted us to evaluate the involvement of NGB in the E2/ERα‐induced low sensitivity of MCF‐7 cells to paclitaxel‐induced apoptosis. Indeed, we recently demonstrated that NGB is an E2/ERα‐dependent compensatory protein, in which upregulation counteracts apoptosis induced by oxidative stress in several cancer cell lines . Data shown in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Data shown in Fig. A indicate that the ERα activation is necessary to increase NGB levels in MCF‐7 cells , as demonstrated by the ability of the ERα agonist PPT (10 nM, 24 h) to mimic the E2 effect. Although paclitaxel does not modify ERα levels and activity (see Fig.…”
Section: Resultsmentioning
confidence: 85%
“…O 2 binding/supply, the metabolism of reactive nitrogen and oxygen species, apoptosis through different pathways, intracellular signaling, and cell protection during hypoxia and ischemia (1)(2)(3)(4)(5)(6). Besides the central and peripheral nervous system and retina, Ngb is also expressed in endocrine tissues, hematopoietic stem cells, the gastrointestinal tract, and cancer cells (7,8). Although the first publication on the subject was in 2000, the in vivo role of Ngb is still uncertain.…”
Section: Neuroglobin (Ngb)mentioning
confidence: 99%